Solve for the determinants: $\begin{vmatrix}1 & 2 & 3 \\ 2 & -1 & 4 \\-1 & -1 & -5\end{vmatrix}$ Solve for the determinant of $\begin{vmatrix} 1 & 2 & 3 \\ 2 & -1 & 4 \\ -1 & -1 & -5 \end{vmatrix}$ A. 10 C. 14 B. 12 D. 16 Log in or register to post comments Solution Click here to… Jhun Vert Fri, 06/07/2024 - 18:23 Solution Click here to expand or collapse this section $D = \begin{vmatrix} 1 & 2 & 3 \\ 2 & -1 & 4 \\ -1 & -1 & -5 \end{vmatrix}$ $D = \left| \begin{matrix} 1 & 2 & 3 \\ 2 & -1 & 4 \\ -1 & -1 & -5 \\ \end{matrix} \left| \, \begin{matrix} 1 & 2 \\ 2 & -1 \\ -1 & -1 \\ \end{matrix} \right. \right|$ $D = \text{Sum of product of downward diagonals} - \text{Sum of product of upward diagonals}$ $D = \left[ 1(-1)(-5) + 2(4)(-1) + 3(2)(-1) \right] - \left[ -1(-1)(3) + (-1)(4)(1) + (-5)(2)(2) \right]$ $D = (5 - 8 - 6) - (3 - 4 -20)$ $D = -9 - (-21)$ $D = -9 + 21$ $D = 12$ Recommended Solution Use the matrix function of your calculator Log in or register to post comments

Solution Click here to… Jhun Vert Fri, 06/07/2024 - 18:23 Solution Click here to expand or collapse this section $D = \begin{vmatrix} 1 & 2 & 3 \\ 2 & -1 & 4 \\ -1 & -1 & -5 \end{vmatrix}$ $D = \left| \begin{matrix} 1 & 2 & 3 \\ 2 & -1 & 4 \\ -1 & -1 & -5 \\ \end{matrix} \left| \, \begin{matrix} 1 & 2 \\ 2 & -1 \\ -1 & -1 \\ \end{matrix} \right. \right|$ $D = \text{Sum of product of downward diagonals} - \text{Sum of product of upward diagonals}$ $D = \left[ 1(-1)(-5) + 2(4)(-1) + 3(2)(-1) \right] - \left[ -1(-1)(3) + (-1)(4)(1) + (-5)(2)(2) \right]$ $D = (5 - 8 - 6) - (3 - 4 -20)$ $D = -9 - (-21)$ $D = -9 + 21$ $D = 12$ Recommended Solution Use the matrix function of your calculator Log in or register to post comments

## Solution Click here to…